STRATEGIES TO INCREASE THE ACOUSTICAL QUALITY OF THE MOSQUES WITHOUT REINFORCEMENT SYSTEM - Setiyowati, Ernaning (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2010)
One of the criteria of a good mosque is a good quality of building acoustic for some ibadah purposes, such as prayer and Friday speech. Mosques with medium size actually need no reinforcement system yet. Unfortunately, most of Indonesian mosques’ typological form were given very little attention about their acoustical problem. Such problems have found in almost every mosques. Therefore, some strategies are needed to fix the problem. Those strategies can be practiced on mosque’s interior surfaces such as ceiling, walls, and floor. One of the strategy is using the absorption material on the wall and the floor, beside using the reflection material on the ceiling. The placement of those materials depends on the path of the sound. The strategy can be used in every form of mosque with only little different treatment in each mosque’s form. With this strategy, it is expected that mosques with medium size will no longer use the reinforcement system, yet the voice still can reach all of the jamaah. Thus this strategy can be used to reduce the use of energy in these buildings.